GeO2 dopant induced enhancement of red emission in CaAl12O19:Mn4+ phosphor - Shu, Wei; Jiang, Lingling; Xiao, Siguo; Yang, Xiaoliang; Ding, J.W. (Materials science & engineering. B, Solid-state materials for advanced technology, 2012)
In order to search efficient red-emitting phosphors for white LEDs application, CaAl12O19:Mn4+ phosphors have been prepared by a combustion method assisted with GeO2 flux. The influence of GeO2 concentration and annealing temperature on the structure and luminescence intensity for the phosphors has been investigated. The mechanism for luminescence enhancement has been discussed. At GeO2 doping concentration of 1.5mol%, the red emission intensity increases by 81% under 330nm UVA excitation. More isolated luminescence center Mn4+ ions rather than pairs of Mn4+-Mn2+ ions are formed in the lattice with the introduction of GeO2 at high temperature oxidation, leading to the enhancement of the red emission. A feasible new way to enhance the red emission in CaAl12O19:Mn4+ phosphor is obtained.